Innovative heat pipe-based photovoltaic/thermoelectric (PV/TEG) generation system - Makki, Adham (2017)
PV systems in practice experience excessive thermal energy dissipation that is inseparable from the photo-electric conversion process. The temperature of PV cells under continuous illumination can approach 40°C above ambient, causing a drop in the electrical performance of about 30%. The significance of elevated temperature on PV cells inspired various thermal management techniques to improve the operating temperature of the cells and hence their conversion efficiency. Hybrid PV/Thermal (PV/T) collectors that can supply both electrical and thermal energy are attractive twofold solution, being able to cool the PV cells and thus improving the electrical power output as well as collecting the thermal energy by-product for practical utilization. The challenges present on the performance of PV systems due to elevated operating temperature is considered the research problem within this work. In this research, an integrated hybrid heat pipe-based PV/Thermoelectric (PV/TEG) collector is proposed and investigated theoretically and experimentally. The hybrid collector considers modular integration of a PV absorber rated at 170W with surface area of 1.3 m2 serving as power generator as well as thermal absorber. Five heat pipes serving as the heat transport mediums were attached to the rear of the module to extract excessive heat accumulating on the PV cells. The extracted heat is transferred via boiling-condensation cycle within the heat pipe to a bank of TEG modules consisting of five 40 mm x 40 mm modules, each attached to the condenser section of each heat pipe. In principle, the incorporation of heat pipe-TEG thermal waste recovery assembly allow further power generation adopting the Seebeck phenomena of Thermoelectric modules. A theoretical numerical analysis of the collector proposed is conducted through derivation of differential equations for the energy exchange within the system components based on energy balance concepts while applying explicit finite difference numerical approach for solutions. The models developed are integrated into MATLAB/SIMULINK environment to assess the cooling capability of the integrated collector as well as the addition power generation through thermal waste heat recovery. The practical performance of the collector proposed is determined experimentally allowing for validation of the simulation model, hence, a testing rig is constructed based on the system requirements and operating principles. Reduction in the PV cell temperature of about 8°C, which account for about 16% reduction in the PV cell temperature response compared to a conventional PV module under identical conditions is attained. In terms of the power output available from the PV cells, enhanced power performance of additional 5.8W is observed, contributing to an increase of 4% when compared with a PV module. The overall energy conversion efficiency of the integrated collector was observed to be steady at about 11% compared to that of the conventional PV module (9.5%) even at high ambient temperature and low wind speeds. Parametric analysis to assess the performance enhancements associated to the number of heat pipes attached to the PV module is conducted. Increasing the number of heat pipes attached to 15 pipes permits improved thermal management of the PV cells realised by further 7.5% reduction in the PV module temperature in addition to electrical output power improvement of 5%.